2022
DOI: 10.1038/s41598-022-18025-x
|View full text |Cite|
|
Sign up to set email alerts
|

3D transcranial ultrasound localization microscopy for discrimination between ischemic and hemorrhagic stroke in early phase

Abstract: Early diagnosis is a critical part of the emergency care of cerebral hemorrhages and ischemia. A rapid and accurate diagnosis of strokes reduces the delays to appropriate treatments and a better functional recovery. Currently, CTscan and MRI are the gold standards with constraints of accessibility, availability, and possibly some contraindications. The development of Ultrasound Localization Microscopy (ULM) has enabled new perspectives to conventional transcranial ultrasound imaging with increased sensitivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Planewave sequences can be used for ultrafast imaging at very high frame-rates, which are useful to a number of imaging modalities, including power Doppler [22], super-resolution [21], elastography [64], and more. These modalities may be used for diagnosis of stroke [65], aneurysm [6], and tumor identification [64]. The significant advantage of this transducer in these imaging modalities is its large FOV, which would enable a single probe placement to cover a large portion of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Planewave sequences can be used for ultrafast imaging at very high frame-rates, which are useful to a number of imaging modalities, including power Doppler [22], super-resolution [21], elastography [64], and more. These modalities may be used for diagnosis of stroke [65], aneurysm [6], and tumor identification [64]. The significant advantage of this transducer in these imaging modalities is its large FOV, which would enable a single probe placement to cover a large portion of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of PCCAs could be broad or selective, with the latter making vascular connections visible without further processing. Three-dimensional ULM has already been shown capable of discriminating between ischemic and hemorrhagic stroke 26 . Three-dimensional AWSALM may add additional value by being able to detect vascular connectivity, for example, collateral vasculature that serves as a natural bypass in response to reduced or blocked blood flow, 32 and by being able to follow the flow from the source to the peripheral vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…In brain studies in particular, 2D ULM was shown to retrieve blood flow parameters such as cerebral vascularity, mean blood velocity and vessel tortuosity in an Alzheimer's mouse model (Lowerison et al 2022), and systolic and diastolic velocities in the human brain (Demené et al 2021). The method was also tested to characterize strokes in the rodent brain, in both 2D (Hingot et al 2020) and 3D (Chavignon et al 2022b). In silico, it was shown that microbubble tracks in ULM could even contain more information such as the pulsatility (Wiersma et al 2022).…”
Section: Introductionmentioning
confidence: 99%